Becoming an expert carer: the process of family carers learning to manage technical health procedures at home. (26th April 2016) - McDonald, Janet; McKinlay, Eileen; Keeling, Sally; Levack, William
Abstract: Aims: To describe the learning process of family carers who manage technical health procedures (such as enteral tube feeding, intravenous therapy, dialysis or tracheostomy care) at home. Background: Increasingly, complex procedures are being undertaken at home but little attention has been paid to the experiences of family carers who manage such procedures. Design: Grounded theory, following Charmaz's constructivist approach. Methods: Interviews with 26 family carers who managed technical health procedures and 15 health professionals who taught carers such procedures. Data collection took place in New Zealand over 19 months during 2011–2013. Grounded theory procedures of iterative data collection, coding and analysis were followed, with the gradual development of theoretical ideas. Findings: The learning journey comprised three phases: (1) an initial, concentrated period of training; (2) novice carers taking responsibility for day‐to‐day care of procedures while continuing their learning; and (3) with time, experience and ongoing self‐directed learning, the development of expertise. Teaching and support by health professionals (predominantly nurses) was focussed on the initial phase, but carers' learning continued throughout, developed through their own experience and using additional sources of information (notably the Internet and other carers). Conclusion: Further work is needed to determine the best educational process for carers, including where to locate training, who should teach them, optimal teaching methods and how structured or individualized teaching should be. Supporting carers well also benefits patient care.